Polythioether Particles Armored with Modifiable Graphene Oxide Nanosheets. Issue 11 (14th April 2016) - Rodier, Bradley J.; Mosher, Eric P.; Burton, Spencer T.; Matthews, Rachael; Pentzer, Emily
Abstract : Facile and scalable fabrication methods are attractive to prepare materials for diverse applications. Herein, a method is presented to prepare cross‐linked polymeric nanoparticles with graphene oxide (GO) nanosheets covalently attached to the surface. Alkene‐modified GO serves as a surfactant in a miniemulsion polymerization, and the alkene functionalities of GO exposed to the oil‐phase are incorporated into the polymer particle through thiol‐ene reactions, leaving the unreacted alkene functional groups of the other face of GO available for further functionalization. The surface of GO‐armored polymer particles is then modified with a small molecule fluorophore or carboxylic acid functional groups that bind to Fe2 O3 and TiO2 nanoparticles. This methodology provides a facile route to preparing complex hybrid composite materials. Abstract : Nanosheets of graphene oxide (GO) are used here as a surfactant in miniemulsion polymerization and are covalently incorporated onto the surface of polymer particles. The exposed surface of the GO nanosheets is then modified with a small molecule fluorophore or functional group that can bind to inorganic nanoparticles. This methodology provides a facile and simple route to hybrid materials.